PARENTS INVOLVEMENT ON CHILDREN’S EDUCATION AT ELEMENTARY SCHOOL IN OMESURI, LEMBATA REGENCY - Ramadhan Jamhar; Sunu Hastuti (UIBU, 2019)
This study was done to know the parents’ involvement on children’s education at elementary school in Omesuri, Lembata Regency. The aim of the study is to ascertain how does parental involvement on students elementary education. In this case study, a qualitative research was used. Data was gathered by interviewing parents of five differents elementary school in Omesuri, who all have children that have good achivement in academic. The study found that all participants are all highly involved with their children’s education. However, not all aspects the parents involved. There were three of six aspects that the parents involved, namely parenting, communication, and learning at home. While the other three aspects were not involved, namely volunteering, decision making, and collaborating with community. The study showed that parental involvement has positive effects on students’ academic achievement on Elementary Schools in Omesuri.